Mapping the research landscape of intra-articular knee injections: a bibliometric analysis using the Scopus database - Musa, Abdullah Aqeel; Low, Chooi Leng; Siron @ Baharom, Khairul Nizam; Mohamad Nazarallah, Mohamad Hilmi; Kow, Ren Yi; Abu Bakar, Intan Bazilah; Halim Lim, Aidi Aswadi; Zulkifly, Ahmad Hafiz (Springer Nature, 2024)
Intraarticular injection of osteoarthritis knee is one of the treatment options for pain management and delays the need for knee surgery. Various materials have been promoted for the procedure, ranging from corticosteroid to viscosupplement to the more recent autologous biological materials. Despite the increasing attention and interest in regard to the material selection, efficacy, safety, and effect of this intervention, a comprehensive bibliometric analysis using the Scopus database has yet to be conducted. In this bibliometric analysis, we reviewed the Scopus database from 2003 to 2023 to investigate the literature on intraarticular injection for the treatment of knee osteoarthritis. A total of 1,318 articles that satisfied the selection criteria were included in this review. The trend of intervention shows changes since 2006, with corticosteroid injection and hyaluronic acid as the main topics of publication before 2006. However, starting in 2010, there has been a noticeable shift towards biological agents, such as plasma-rich proteins, and autologous materials, including marrow aspiration and stromal vascular fraction. This shift reflects the increasing interest in regenerative medicine and the potential of these newer therapies to provide improved outcomes. The overwhelming majority of the articles were authored by researchers and clinicians from across European countries, the United States of America (USA), and Australia. Similarly, most of the articles with the highest number of citations were authored by researchers and clinicians from these regions. This comprehensive bibliometric analysis using Scopus in the domain of intraarticular injection has the potential to act as a roadmap for researchers, clinicians, and policymakers, facilitating informed decision-making, promoting collaborative initiatives, and guiding the development of future studies to further advance the options of knee intraarticular injection, specifically in the management of knee osteoarthritis.